1998
DOI: 10.1103/physrevlett.81.2723
|View full text |Cite
|
Sign up to set email alerts
|

Sevenfold Coordinated MgSe: Experimental Internal Atom Position Determination to 146 GPa, Diffraction Studies to 202 GPa, and Theoretical Studies to 500 GPa

Abstract: MgSe has been studied using energy dispersive x-ray diffraction to 202 GPa and local density approximation and ultrasoft pseudopotentials to 500 GPa. MgSe undergoes a "continuous" phase transformation from the rocksalt to FeSi (B28) beginning at around 99 6 8 GPa and approaching sevenfold coordination at 202 GPa. Theoretical computation finds the B28 transition beginning at 58 GPa followed by a transition to an orthorhombic distortion of the B2 structure at 429 GPa.[S0031-9007(98)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 22 publications
4
17
0
Order By: Relevance
“…[18] microscopic point of view. The calculated equilibrium lattice constants a, elastic constants C ij , zero-pressure bulk modulus B 0 and its pressure derivation B 0 from the Birch-Murnaghan equation of state (EOS) [17] are listed in Table 1, together with other theoretical results [5][6][7][18][19][20][21][22][23][24][25][26][27]4] and the experimental data [28]. The agreements among them are good.…”
Section: Resultsmentioning
confidence: 94%
“…[18] microscopic point of view. The calculated equilibrium lattice constants a, elastic constants C ij , zero-pressure bulk modulus B 0 and its pressure derivation B 0 from the Birch-Murnaghan equation of state (EOS) [17] are listed in Table 1, together with other theoretical results [5][6][7][18][19][20][21][22][23][24][25][26][27]4] and the experimental data [28]. The agreements among them are good.…”
Section: Resultsmentioning
confidence: 94%
“…Electronic band structure studies of these systems specifies that there are no d electrons available in the valence band and a energy gap of about 2.5-6 eV is documented. Under compression, a first-order phase transition from the sixfold-coordinated B1 structure to the eightfold-coordinated CsCl-type (B2) has been found in magnesium chalcogenides MgX (X ¼ S, Se, and Te) [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Ruoff et al [7] have studied MgSe using energy dispersive X-ray diffraction (EDXD) to 202 GPa and local density approximation and ultrasoft pseudopotential to 500 GPa. It is revealed that MgSe undergoes a continuous phase transformation from the rocksalt to FeSi (B28) beginning at around 9978 GPa and approaching sevenfold coordination at 202 GPa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a theoretical prediction of the phase transition from the NiAs structure to the orthorhombic Pnma structure above 43 GPa has been published [101] despite no transition was found up to 60 GPa [100]. On the other hand, MgSe has been found to transit from the rocksalt to the FeSi structure around 100 GPa in relatively good agreement with calculations [102,103].…”
Section: Ax Compoundsmentioning
confidence: 80%